Answer:
[tex]\therefore 2\dfrac{1}{3} \div \left ( -3\dfrac{2}{3} \right ) = -\dfrac{7}{11}[/tex]
Step-by-step explanation:
The question relates to dividing a fraction by proper and another fraction
The given expression is presented as follows;
[tex]2\dfrac{1}{3} \div \left ( -3\dfrac{2}{3} \right )[/tex]
We rearrange the fractions as improper fractions for easier division as follows;
[tex]2\dfrac{1}{3} = \dfrac{7}{3}[/tex]
[tex]-3\dfrac{2}{3} = -\dfrac{11}{3}[/tex]
Therefore, we have;
[tex]2\dfrac{1}{3} \div \left ( -3\dfrac{2}{3} \right ) = \dfrac{7}{3} \div \left (-\dfrac{11}{3} \right ) = \dfrac{7}{3} \times \left (\dfrac{1}{-\dfrac{11}{3} } \right ) = \dfrac{7}{3} \div \left (-\dfrac{3}{11} \right ) =-\dfrac{7}{11}[/tex]
[tex]\therefore 2\dfrac{1}{3} \div \left ( -3\dfrac{2}{3} \right ) = -\dfrac{7}{11}[/tex]